Experimental analysis of the effects of laser surface texturing on tribological properties of PTFE/Kevlar fabric composite weave structures. (July 2019) - Qi, Xiaowen; Wang, Hai; Dong, Yu; Fan, Binli; Zhang, Wenli; Zhang, Yan; Ma, Jian; Zhou, Yefei
Abstract: Laser surface texturing (LST) has been proved to be exceedingly effective in reducing friction and wear in a tribosystem, but there is very little research carried out on the application and research of LST in dry friction. In this study, the round dimple-like LST was fabricated on 45# steel surface and its effect on tribological properties of PTFE/Kevlar fabric composite weave structures was thoroughly investigated in dry friction. The associated results showed that the utilization of preferable microconcave parameters consisting of 100 μm in diameter, 30% in area density and 0.1 for the depth-diameter ratio could decrease the friction coefficient and wear rate by 64 and 82%, respectively when compared with those for untextured surfaces. In addition, different parameter of microconcaves appeared to induce significant impact with mutual interactions to affect the LST. It was found that the LST tended to accelerate the formation of transfer films due to the storage feature of microconcaves for improving the tribological properties. The long period test results suggest that the coefficient of friction will change after a period about an hour (sliding distance of 1000 m), that is to say, after about 23 h, untextured surfaces would be basically the same as the friction coefficient of textured ones. Highlights: Optimum LST can be of great significance to enhance the friction properties. The wear debris can be captured and collected rapidly in LST microconcaves. Interactions between geometrical LST parameters have significant effects. Untextured surfaces have the same friction coefficient after long period test. LST help quickly form and maintain a transfer film.